2013
DOI: 10.1108/ilt-10-2012-0116
|View full text |Cite
|
Sign up to set email alerts
|

Static performance characteristics of hybrid journal bearings with plugged entry holes

Abstract: PurposeThis paper aims to investigate the effect of plugging of holes on the static performance characteristics of a constant flow valve compensated hole‐entry hybrid journal bearing system operating with Newtonian and non‐Newtonian lubricants. The analysis considers the generalized Reynolds equation governing the flow of lubricant having variable viscosity in the clearance space and equation of flow of lubricant through constant flow valve restrictor. The non‐Newtonian lubricant is assumed to follow the power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The results showed the decrease in static performance characteristics such as pressure intensity, load-carrying capability, friction force and temperature for pseudo-plastic lubricant whereas these characteristics increased for the dilatant lubricant. Garg and Kumar [9] investigated the influence of blocking of holes on the static performance characteristics of hybrid journal bearing operated with powerlaw lubricants using flow behaviour index (n = 1 and 0.566). It was found that the journal bearing with blocked holes provided more lubricant film thickness and load-carrying capability of the journal bearing.…”
Section: Power-law Lubricantsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results showed the decrease in static performance characteristics such as pressure intensity, load-carrying capability, friction force and temperature for pseudo-plastic lubricant whereas these characteristics increased for the dilatant lubricant. Garg and Kumar [9] investigated the influence of blocking of holes on the static performance characteristics of hybrid journal bearing operated with powerlaw lubricants using flow behaviour index (n = 1 and 0.566). It was found that the journal bearing with blocked holes provided more lubricant film thickness and load-carrying capability of the journal bearing.…”
Section: Power-law Lubricantsmentioning
confidence: 99%
“…The blocking of holes was not recommended due to high wear rate during starting and stopping of operation. The fluid film thickness (h) for journal bearings was determined by using Equation (2) [5,9,10];…”
Section: Power-law Lubricantsmentioning
confidence: 99%
See 2 more Smart Citations